Additive manufacturing of AA2024/Al2O3 nanocomposites via friction surfacing: Investigating metallurgical, mechanical, and tribological properties - Milad Abbasi Nahr; Seyyed Ehsan Mirsalehi; Ahmad Papi (Journal of Materials Research and Technology)
Friction surfacing (FS) is a solid-state additive manufacturing method that uses high-temperature plastic deformation to produce fully dense multilayer samples with a fine-grained microstructure. This study uses the FS process to fabricate composite samples of AA2024-T4 reinforced with 1.5 wt% nano-Al2O3 alongside non-composite counterparts for comparison. This study aims to improve microstructure by examining deposition parameters, including rod rotational speeds (600–1200 rpm), travel speed (70–85 mm/min), and feeding rate (30–45 mm/min), which affect the heat input during FS. Evaluations of the consumable rod and deposition multilayer samples included macro- and microstructural analyses using OM, XRD, and SEM equipped with EDS, along with evaluation of hardness and wear properties. Results demonstrated that successfully produced defect-free multilayer AA2024/Al2O3 nanocomposites with well-bonded layers, uniform Al2O3, and precipitates distribution, fragmented intermetallic compounds, and fine-grained microstructure with an average grain size of 3–10 μm. The FS-produced composites exhibited improved hardness and wear resistance compared to non-composites. Increasing rotational speed widened samples (3.7 mm) and reduced thickness (4.56 mm). The optimal microstructure, achieved at a rotational, traverse and feed speed of 1000 rpm, 80 mm/min, and 40 mm/min, features a grain size of 3.74 ± 1.01 μm, a hardness of 123.75 ± 9.28 HV, and a wear rate of 6.6 × 10−4 mg/N·m. Additionally, of the 14 samples produced, this particular sample showed a hardness increase of 20.5 % and 20.3 %, a grain size reduction of 22.9 % and 17.8 %, and a wear rate decline of 5.7 % and 12.9 % compared to the non-composite counterpart and the highest-performing samples, respectively.